PENILAIAN SAHAM PT MATAHARI PUTRA PRIMA Tbk PASCA DIVESTASI MATAHARI DEPARTEMENT STORE TAHUN 2010 - , Herdaru Marseno, B.S.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research tend to estimate intrinsic value of share of PT Matahari Putra Prima Tbk (MPPA) after divestment of Matahari Department Store using income approach with discounted cash flow method and market approach (relative valuation). Income approach using data from PT Matahari Putra Primaâs financial report form 2006 to September 30, 2010. The analysis of discounted cash flow method conducted by analyzing the projection of sales, balance sheet, determining discount factor, projecting free cash flow, and estimating value. Market approach analysis started by choosing comparable companies in the same line of business to determine suitable multiples for converting book value of MPPA variables into market value estimation. The result of using income approach is Rp1.557,88 while market approach resulting value of Rp1.247,16. Reconciliation of both values delivers Rp1.464,67 as the intrinsic value of MPPA. Based on these value can be concluded that the value of MPPA after the divestment of Matahari Department Store is in fair value.